Aquinas on transubstantiation: the real presence of Christ in the Eucharist - Hütter, Reinhard (Thomistic ressourcement series, 2019)
Mysterium fidei: the mystery of faith proposed in scripture -- Dogma datur christianis: the truth is given to Christians by tradition and the Magisterium -- Eucharistic conversion and the categories "substance" and "quantity" -- "This is my body": faith preserves the intellect from deception -- "You are my friends": Christ's Eucharistic presence, central token of Christ's surpassing friendship.